Effects of the Technology-Enhanced Lessons in Optics (TELO) on the Academic Performance of Grade 10 Students - Calzada, Marc Paul T.; Antonio , Vida V. (International Journal of Multidisciplinary: Applied Business and Education Research, 2024)
This study investigated the effects of Technology-enhanced Lessons in Optics (TELO) on the academic performance of grade 10 students. A researcher-made Physics Achievement Test was used to measure student performance, and mean scores were utilized to describe the student’s performance in both pretests and post-tests. The study employed statistical tests, including the t-test of difference between dependent samples and the t-test of difference between means of two independent samples, to analyze the data. During the 2nd Quarter of the School Year 2022-2023, the Technology-enhanced Lessons in Optics (TELO) intervention was implemented for twenty meetings with grade 10 Science, Technology, and Engineering students. The control and experimental groups, consisting of two heterogeneous students, were randomly assigned. Pretest and post-test scores showed a significant improvement in both groups, indicating the acquisition of knowledge and skills. However, the experimental group achieved significantly higher scores in the post-test. TELO's interactive features and ICT-based instruction facilitated active learning and enhanced student performance. The study provides evidence for the effectiveness of TELO in improving the academic performance of grade 10 students, highlighting the value of interactive and ICT-based approaches grounded in constructivist principles and the SAMR model in enhancing Physics learning outcomes.